An Intronic Alu Element Attenuates the Transcription of a Long Non-coding RNA in Human Cell Lines - Pérez-Molina, Rosario; Arzate-Mejía, Rodrigo G.; Ayala-Ortega, Erandi; Guerrero, Georgina; Meier, Karin; Suaste-Olmos, Fernando; Recillas-Targa, Félix (Frontiers in Genetics, 2020)
Alu elements are primate-specific repeats and represent the most abundant type of transposable elements (TE) in the human genome. Genome-wide analysis of the enrichment of histone post-translational modifications suggests that human Alu sequences could function as transcriptional enhancers; however, no functional experiments have evaluated the role of Alu sequences in the control of transcription in situ. The present study analyses the regulatory activity of a human Alu sequence from the AluSx family located in the second intron of the long intergenic non-coding RNA Linc00441, found in divergent orientation to the RB1 gene. We observed that the Alu sequence acts as an enhancer element based on reporter gene assays while CRISPR-Cas9 deletions of the Alu sequence in K562 cells resulted in a marked transcriptional upregulation of Linc00441 and a decrease in proliferation. Finally, genome-wide analyses revealed that lincRNAs with intragenic Alu sequences show overall lower levels of transcription than the ones lacking Alu sequences. Our results suggest that intragenic Alu elements with enhancer activity act as transcriptional attenuators of their host lincRNAs.